PENGARUH KONDISI LENGAS TANAH DAN MEDIA TUMBUH YANG BERBEDA TERHADAP PERTUMBUHAN DAN HASIL KACANG HIJAU (VIGNA RADIATA L.) - CATHARINA, THERESIA SUZANNA; DETHAN, STEVANY HANALYNA; MEIKAPASA, NI WAYAN PUTU (GANEC SWARA, 2022)
This study aims to determine the effect of soil moisture conditions and different growing media on the growth and production of mung bean (vigna radiata L.). The method used in this research is an experimental method by experimenting with planting in pots in a plastic house. The experiment was carried out in a green house that was prepared on farmer's land, Mataram District, East Pagutan Village, Karang Buaya Village. The experiment was planned for 4 months. The experimental design used was a completely randomized design by arranging the treatment in a factorial manner, which consisted of 2 treatment factors as follows: origin of the growing medium (entisols) (M), with 3 levels as follows: M1 = growing medium from Sayong village, M2 = medium growing from Kuripan village and M3 = growing medium from Bayan. Moisture content with 2 treatment levels of water supply, namely: C1 = water supply 100% moisture content. . C2 = 50% moisture content of water, thus 6 treatment combinations were obtained and each treatment combination was repeated three times, so 18 experimental pots were obtained.The results showed that the best growth of mung bean on growing media was from Kuripan with 100% moisture content, while at 50% moisture content from Bayan. The highest yield of green beans in growing media was from Bayan at 100% soil moisture, while 50% moisture content in growing media from Saiyong.